Unconditional finite amplitude stability of a viscoelastic fluid in a mechanically isolated vessel with spatially non-uniform wall temperature - Dostalík, Mark; Průša, Vít; Stein, Judith (Mathematics and computers in simulation, 2021)
We investigate finite amplitude stability of spatially inhomogeneous steady state of an incompressible viscoelastic fluid which occupies a mechanically isolated vessel with walls kept at spatially non-uniform temperature. For a wide class of incompressible viscoelastic models including the Oldroyd-B model, the Giesekus model, the FENE-P model, the Johnson-Segalman model, and the Phan-Thien-Tanner model we prove that the steady state is stable subject to any finite perturbation.
Gesehen am 17.06.2022
Available online 16 May 2020, Version of Record 9 August 2021